Proceso de atención de enfermería domiciliario en paciente diabético de 56 años con sars-covid19. - Castillo Monsalve, Armando Gilberto (2021)
Diabetes is a pathology that seriously affects Ecuador, being the third leading cause of death in the country, an indicator that should promote people to have a better quality of food, in order to avoid suffering from this disease, since it involves many complications. As it is known today that the current pandemic caused by SARS-CoV2 or also know as Covid 19 belongs to the family of coronaviruses which is a new mutated strain, which are still conducting research to find a specific treatment. People who have overcome on suffered from this disease do not really know the repercussions or conditions that it can present in the body in the long term. Covid 19 in a highly infections pathology that can manifest itself from the most moderate to chronic symptoms, it should be noted that patients with underlying diseases such as Diabetes Mellitus are vulnerable to the presence of this virus. The following clinical case study focuses on a 58 years-old Diabetic patient with Covid 19, at the same time that a correct home care plan is developed with the help of a family doctor, all biosafety measure are taken, in order to do so. Offer you quality care and warmth and obtain your speedy recovery.